Is jellyfish a suitable ingredient for aquafeed? A comprehensive review of nutritional potential and limitation - Guttuso, Paolo; Nogueira, Natacha; Gueroun, Sonia K. M.; Javidpour, Jamileh; Canning-Clode, João; Andrade, Carlos A. P. (Frontiers in Marine Science, 2025)
Jellyfish’s potential for feed production remains largely unexplored and research on their nutritional benefits in aquafeeds is still limited. This systematic review analyzed the nutritional composition of jellyfish and its potential as a sustainable aquaculture feed ingredient, evaluating advantages and limitations. Data from 65 studies were categorized into proximate composition, amino acids, fatty acids, and mineral content. Good proportion of methionine and lysine, high amount of collagen-derived amino acids (glycine, proline, hydroxyproline), the presence of taurine and beneficial long-chain fatty acids (mainly ARA), as well as richness in minerals such as Na, K, Cl, Mg, and Zn, constitute attractive key characteristics for feed application. However, challenges remain, including high moisture and ash content, elevated aluminum levels from present processing methods, and compositional variability. Improved processing methods may enhance their use, but further research is needed to address digestibility, optimize processing, and assess long-term sustainability. This study positions jellyfish as a valuable, sustainable supplement for aquaculture feed, though comprehensive evaluations are necessary to unlock their full potential and ensure consistent quality in commercial applications.